PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERKEBUNAN KABUPATEN MAMUJU UTARA - Rusmawita, Rusmawita (Katalogis, 2016)
The purpose of this study was to determine the effect of motivation and work environment on employee performance. This research uses explanatory research type pattern in explaining the relationship between the variables under study, involving 36 Employees Plantation Office North Mamuju taken with census techniques. The problems of this study: 1) To determine and analyze the influence of motivation and work environment simultaneously positive and significant impact on employee performance; 2) To determine and analyze the influence of motivation partially positive and significant impact on employee performance; 3) To know and analyze the influence of the working environment is partially positive and significant impact on employee performance. Based on test results using multiple regression analysis Adjust R-Square value of 0.638 or 63.80% dependent variable is affected by the three independent variables. Based on test results using multiple regression analysis, concluded: 1) motivation and environment kerjasecara simultaneous positive and significant impact on employee performance; 2) motivasisecara partial positive and significant effect on employee performance; 3) The work environment is partially positive and significant impact on employee performance